Quasilinearization for resonant boundary-value problems with mixed boundary conditions - Sveikate, N.; Sadyrbaev, F. (Нелінійні коливання, 2014)
We consider resonant problems of the type (i) x′′ + p(t)x′ + q(t)x = f (t, x, x′), (ii) x′(0) = 0, x(T) = 0, where p, q, f are continuous functions and the homogeneous problem (iii) x′′ + p(t)x′ + q(t)x = 0 with boundary-value conditions (ii) has a nontrivial solution. We study this problem by modifying the linear part and applying the quasilinearization technique to the modified problem. Розглянуто задачi типу (i) x′′ + p(t)x′ + q(t)x = f (t, x, x′), (ii) x′(0) = 0, x(T) = 0, з резонансом, де p, q, f — неперервнi функцiї та однорiдна задача (iii) x′′ + p(t)x′ + q(t)x = 0 разом з граничними умовами (ii) має нетривiальний розв’язок. Задача вивчається за допомогою змiни лiнiйної частини та застосування технiки квазiлiнеаризацiї до модифiкованої задачi.